Low-Cost WS2 Photodetector on Water-Soluble Paper for Transient Electronics - Coleman, Jonathan (My University, 2025)
The rapid development of technology has led to a significant increase in the production of electronic devices, raising concerns about electronic waste (e-waste). Transient electronics, i.e., devices designed to disappear or dissolve after use. Offer a promising route to mitigate this challenge. Here, the first demonstration of a transient photodetector is reported based on direct abrasion-deposited WS2 on water-soluble paper, using graphite electrodes drawn directly on the substrate. The whole device can physically disappear in water in ≈60 s, and the electronic materials can be recovered by vacuum filtration. The device shows a photoresponsivity of ≈176 μA W−1 under ambient conditions.
PUBLISHED
Cited by: 0